Impacts of liner shipping connectivity and global competitiveness on logistics performance: the mediating role of the quality of port and infrastructure - Chen, Yan-Chun; Hasan, Mohammad Kamrul (Transport, 2023)
Logistics Performance (LP) is one of the fundamental catalysts that serve as a podium for the integration of the world economy. This study is conducted to observe the combined effects of Liner Shipping Connectivity (LSC) and Global Competitiveness Index (GCI) on LP in mediating the Quality of Port and Infrastructure (PORT). We selected 28 Asian economies and 1 special administrative region (Hong Kong) counting the year of 2007–2018. Partial Least Square – Structural Equation Model (PLS–SEM) with an extension of the Importance–Performance Map Analysis (IPMA) was applied. Empirical evidence derived from the path diagram has revealed that LSC and global competitiveness in mediating the PORT have significant effects of accelerating LP, leading to higher competitiveness in terms of strategic development and yielding better connectivity. Due to limited resources, Asian decision-makers need a guidance to focus on how to improve LP. This work also helps to highlight the dimensions of LSC and global competitiveness factors to be concentrated on and the policies to be implemented in this regard.